Activity of imipenem/relebactam against Gram-negative bacilli from global ICU and non-ICU wards: SMART 2015–2016. (December 2018) - Lob, Sibylle H.; Hoban, Daryl J.; Young, Katherine; Motyl, Mary R.; Sahm, Daniel F.
Highlights: >90% of non-Proteeae Enterobacteriaceae and >80% of MDR isolates from ICUs were susceptible to imipenem-relebactam in most regions. >80% of P. aeruginosa from ICUs were susceptible to imipenem/relebactam in all regions. Isolates from ICUs were typically more resistant than those from non-ICU wards. ICU/non-ICU differences varied across regions and antimicrobial agents. Imipenem/relebactam could provide a valuable therapeutic option in ICUs. Abstract: Objectives: Antimicrobial resistance is increasing worldwide and is especially problematic in ICUs. Relebactam is a new bicyclic diazabicyclooctane β-lactamase inhibitor of class A and C β-lactamases that is in development in combination with imipenem. This study describes geographical resistance patterns among isolates from ICU and non-ICU wards in seven global regions and examines the activity of imipenem/relebactam in these settings. Methods: In 2015–2016, 194 hospitals from 55 countries each collected up to 100 consecutive Gram-negative pathogens from intra-abdominal, 100 from lower respiratory and 50 from urinary tract infections per year. Susceptibility was determined for 45 699 non-Proteeae Enterobacteriaceae (NPE) and 10 834 Pseudomonas aeruginosa using CLSI broth microdilution and breakpoints, with imipenem breakpoints applied to imipenem/relebactam. Results: Isolates from ICUs were more resistant to almost all tested agents across regions and infection sources. The size of the ICU/non-ICU difference varied, with a smaller gap in USA/Canada and South Pacific (regions with highest susceptibility) and for imipenem/relebactam, amikacin and colistin (drugs with highest activity). Susceptibility of NPE to imipenem/relebactam was >90% in ICUs in all regions except Africa (88.2%). Only amikacin exceeded these rates in most regions. Against cefepime-non-susceptible and multidrug-resistant (MDR) NPE from ICUs, imipenem/relebactam maintained activity >90% in three regions and >80% in the remaining regions except Africa (75%). Susceptibility of P. aeruginosa was >90% in ICUs in USA/Canada, South Pacific and Europe and >82% elsewhere. Conclusions: Imipenem/relebactam could provide a valuable therapeutic option in ICUs, especially against MDR isolates and those non-susceptible to other β-lactam antibiotics.